Respuesta :
Answer: y = 24
(5y - 29) = (3y + 19) Distributive Property
5y - 29 = 3y + 19 Subtract 3y from both sides
2y - 29 = 19 Add 29 to both sides
2y = 48 Divide by 2 to both sides
y = 24 Answer!
(5y - 29) = (3y + 19) Distributive Property
5y - 29 = 3y + 19 Subtract 3y from both sides
2y - 29 = 19 Add 29 to both sides
2y = 48 Divide by 2 to both sides
y = 24 Answer!
Simplifying
5y + -29 = 3y + 19
Reorder the terms:
-29 + 5y = 3y + 19
Reorder the terms:
-29 + 5y = 19 + 3y
Solving
-29 + 5y = 19 + 3y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-3y' to each side of the equation.
-29 + 5y + -3y = 19 + 3y + -3y
Combine like terms: 5y + -3y = 2y
-29 + 2y = 19 + 3y + -3y
Combine like terms: 3y + -3y = 0
-29 + 2y = 19 + 0
-29 + 2y = 19
Add '29' to each side of the equation.
-29 + 29 + 2y = 19 + 29
Combine like terms: -29 + 29 = 0
0 + 2y = 19 + 29
2y = 19 + 29
Combine like terms: 19 + 29 = 48
2y = 48
Divide each side by '2'.
y = 24
Simplifying
y = 24
5y + -29 = 3y + 19
Reorder the terms:
-29 + 5y = 3y + 19
Reorder the terms:
-29 + 5y = 19 + 3y
Solving
-29 + 5y = 19 + 3y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-3y' to each side of the equation.
-29 + 5y + -3y = 19 + 3y + -3y
Combine like terms: 5y + -3y = 2y
-29 + 2y = 19 + 3y + -3y
Combine like terms: 3y + -3y = 0
-29 + 2y = 19 + 0
-29 + 2y = 19
Add '29' to each side of the equation.
-29 + 29 + 2y = 19 + 29
Combine like terms: -29 + 29 = 0
0 + 2y = 19 + 29
2y = 19 + 29
Combine like terms: 19 + 29 = 48
2y = 48
Divide each side by '2'.
y = 24
Simplifying
y = 24